Midcourse Guidance Trajectory Planning Method Based on Pseudospectral Sequence Convex Programming - Zhang, Jinlin; Li, Jiong; Lei, Humin; Zhou, Chijun; He, Yangchao; Ji, Boyang (2024 IEEE 25th China Conference on System Simulation Technology and its Application (CCSSTA), 2024)
A method of course planning based on pseudospectral sequence convex programming is proposed to address the issues of slow generation speed, poor trapezoidal discrete fitting accuracy and the lack of a solution to strong equality terminal constraints in fixed time. This paper employs convex programming theory to enhance the efficiency of model solving and variable trust region to reduce the number of iterations. The model is discretized using the pseudo-spectrum method. A relaxation method for terminal constraints is proposed to relax strong equality constraints and constrain them in the performance index, thus ensuring that the trajectory can be generated quickly. The simulation outcomes reveal that the presented approach is capable of swiftly generating midcourse guidance trajectories that adhere to various constraints.